2016
DOI: 10.1136/jmedgenet-2015-103387
|View full text |Cite
|
Sign up to set email alerts
|

The importance of genetic diagnosis for Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy are caused by mutations in the dystrophin-encoding DMD gene. Large deletions and duplications are most common, but small mutations have been found as well. Having a correct diagnosis is important for family planning and providing proper care to patients according to published guidelines. With mutation-specific therapies under development for DMD, a correct diagnosis is now also important for assessing whether patients are eligible for treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
297
3
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(325 citation statements)
references
References 47 publications
6
297
3
19
Order By: Relevance
“…Current standards of care for DMD diagnosis suggest bypassing muscle biopsy and performing genetic testing first 6–8. Since deletions and duplications of one or more exons are identified in the majority of patients, it is most cost-effective to check for these mutations first by multiplex ligation-dependent probe amplification (MLPA) 8. Most centres still perform muscle biopsy when MLPA analysis does not reveal deletions or duplications, to definitely confirm a dystrophinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Current standards of care for DMD diagnosis suggest bypassing muscle biopsy and performing genetic testing first 6–8. Since deletions and duplications of one or more exons are identified in the majority of patients, it is most cost-effective to check for these mutations first by multiplex ligation-dependent probe amplification (MLPA) 8. Most centres still perform muscle biopsy when MLPA analysis does not reveal deletions or duplications, to definitely confirm a dystrophinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant progress made in identifying DMD and the straightforward diagnostic pathway (Bushby et al, 2009; Verma et al, 2010; Ciafaloni et al, 2009), more than 3 decades of research continues to report on the protracted nature of reaching a definitive DMD diagnosis (Aartsma-Rus, Ginjaar & Bushby, 2016; Ciafaloni et al, 2009; Crisp et al, 1982; Firth, 1983; Green & Murton, 1996; Holtzer et al, 2011; Marshall & Galasko, 1995; Parsons, Clarke & Bradley, 2004; van Ruiten, Straub, Bushby & Guglieri, 2014). Past research has shown that parents of boys with DMD often report concerns when their sons are between the ages of 6 months and 3 years due to their child not meeting or regressing in certain developmental milestones (Ciafaloni et al, 2009; Crisp et al, 1982; Firth, 1983; Green & Murton, 1996; Holtzer et al, 2011; Marshall & Galasko, 1995; Parsons et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are usually the first genetic analyses to be performed for a patient with suspected DMD. Then for cases where an exon copy number variant is not identified, or in positive cases where the patient is to be considered for exon-skipping therapy, sequencing of the entire coding region from genomic DNA should be performed [31]. Next generation sequencing (NGS) strategies facilitate this process and can include sub-exomic targeted gene panels or whole exome sequencing [32][33][34].…”
Section: Methodsmentioning
confidence: 99%